Smart Cities: A Pedagogical Proposal for Arduino in Educational Robotics - Delestre, Cecília Sena; Silva, Gabriel Vinicius Rocha; Mingrone, Isaque Almeida; Kurogi, Rodrigo Eidji; Gomes, Thaís Ribeiro; Pazelli, Tatiana F. P. A. Taveira (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2025)
This paper presents a pedagogical proposal for an introductory Arduino course focused on Educational Robotics. Classes are based on the Project-Based Learning (PBL) method-ology, covering technical content on electronics and programming, in addition to drawing parallels with the subjects of the National Common Curricular Base (BNCC) for high school students. The teaching process includes theoretical and practical classes, teamwork, exposure to everyday problems and chal-lenges, integrating the concept of smart cities, where students themselves will have to automate it through pre-structured models.